Pigeonpea Ratooning Trial Under Conservation Agriculture, 2020 - International Maize and Wheat Improvement Center; Zambian Agriculture Research Institute (International Food Policy Research Institute, 2021)
This dataset includes data generated from the on-station trial that was conducted to evaluate the various management methods that are being advocated in the Southern Africa region. The following treatments were used for this trial. - Sole maize continuous; - Full Pigeonpea/maize rotation; - Maize + Pigeonpea full growth no ratooning; - Maize + Pigeonpea, uprooting at harvest and re-seeding every year; - Maize + Pigeonpea, ratooning at harvest and at seeding; - Maize + Pigeonpea, ratooning at harvest and 2 weeks after maize seeding; - Maize + Pigeonpea, ratooning at harvest and 3 weeks after maize seeding; - Maize + Pigeonpea, strip harvest of pigeonpea pods (no ratooning), plant maize and pigeonpea at seeding time, cut pigeonpea at ground level 2 weeks after maize planting; - Maize + Pigeonpea, strip harvest of pigeonpea pods (no ratooning), delay planting of maize by a minimum of 14 days, cut pigeonpea at base, reseed pigeonpea with maize 14 days after the planting window.